DISKURSUS MANAJEMEN PERUBAHAN SEKOLAH: PERGESERAN PARADIGMA, EKPLORASI KESIAPAN GURU, DAN MEMBACA PELUANG BISNIS PENDIDIKAN - Satria, Rachmat; Fauzan, Fauzan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2024)
Organizational change and development occur through a coherent discourse of change to strengthen culture, structure, and process. Today's organizations are moving dynamically to create new approaches to change. Change is important for organizations to compete and meet internal and external demands, in order to continue to exist and be trusted by the community. This article is compiled using a literature review study approach, starting from reviewing theories relevant to educational change management, then conducting a review. Based on the study conducted, it is known that the results of the study emphasize the importance of adaptation to the paradigm shift of the leader's vision in sustainable change management, teacher readiness for change and school innovation is very important in facing the global education reform movement. In other matters, it is necessary to explore future education business opportunities involving issues of commercialization and education business that present challenges in directing education in a sustainable direction.